Stretching variable gear pump - HUANG LIRAN; LIU DAIYI (2020)
The invention discloses a stretching variable gear pump. By stretching or push-pressing an upper pressure oil base and a lower pressure oil base, the size of an oil pressure cavity is changed, at thetime, under the action of an upper pressure spring, the end of a driving gear is always in contact with the upper end of the lower pressure oil base, and under the action of a lower pressure spring, the end of a driven gear is always in contact with the lower end of the upper pressure oil base; at the time, the part between the upper pressure oil base and a gear sleeve is a meshing part of the driving gear, so that sealing of meshing of the driving gear is ensured; the part between the lower pressure oil base and the gear sleeve is the meshing part of the driven gear, so that sealing of meshing of the driven gear is ensured; and the variable displacement of the gear pump is realized, the various transmission needs of a hydraulic system are met, the applicability of a product is improved, the problem that the displ